Examination of methods for evaluating swimming performances using a drop-off index - Noguchi, T.; Demura, S.; Sato, S.; Nahata, M.; Kitabayashi, T.; Osugi, T.; Watanabe, M. (Japanese Journal of Sciences in Swimming and Water Exercise, 2007)
This study aimed to examine the relationship between the drop-off index and swimming performances and to determine its utility in evaluating whole body endurance. The subjects were 106 male university competitive swimmers (age: 19.9±1.1 years, height: 171.8±5.6 cm, weight: 66.2±5.7 kg). Performances in the 200 m drop-off test and 50 m, 100 m, 200 m and 400 m free style swimming tests were analyzed. The drop-off index showed significant correlations (r = 0.48, 0.51, 0.61) with performances in the 100 m, 200 m, and 400 m free style, but not in the 50 m performance. The drop-off test was associated with middle distance swimming performances in the 100 m, 200 m, and 400 m free style. In consideration of its limitations in use, the drop-off test may be effective in estimating swimming performances.